Orchestrating Extracellular Vesicle With Dual Reporters for Imaging and Capturing in Mammalian Cell Culture - Levy, Daniel; Do, Mai Anh; Zhang, Jiayi; Brown, Annie; Lu, Biao (Frontiers in Molecular Biosciences, 2021)
BACKGROUND: Recent technological advancements have enabled live-cell imaging of intracellular organelles to monitor their biogenesis in mammalian cells. However, applying this method to gain insight into extracellular organelles, such as extracellular vesicles (EVs), presents unique challenges that require special considerations in design and engineering. RESULTS: We have developed a dual-reporter system that combines genetic fusion, fluorescence microcopy and magnetic beads capture of EVs to study the biogenesis of EVs in mammalian cell cultures. First, we genetically produced a series of reporters by fusing a green fluorescent protein (GFP) and an affinity peptide (6xHis), with either the endogenous transmembrane protein, CD63, or EVs targeting vesicular stomatitis viral glycoprotein (VSVG). Transfection of these reporters into human 293T cells resulted in expression and integration of these reporters into exosome compartments, which were subsequently released into the culture medium. Confocal imaging and nano-particle tracking analysis demonstrated that EVs were appropriately labeled and exhibited a single dominant peak in the 80~110 nm size range, indicating that isolated EVs were comprised of micro-vesicles and/or exosome subpopulations. Incubation of isolated EVs with nickel-coated magnetic beads resulted in successful capture of GFP-positive EVs. Finally, addition of EVs into culture medium was able to reveal the cellular uptake of GFP-labeled EVs by recipient cells. Taken together, our dual-reporter system provides a powerful method for both monitoring and capturing of EVs in mammalian cell culture systems. CONCLUSIONS: A dual-reporter system provides a robust tool to study the life cycle of EVs in mammalian cells from biogenesis and excretion to cellular uptake.